Aquatic Display: Navigating the Roman Imperial World in Acts 27. (20th November 2015) - Carter, Warren
Abstract : This article reads Acts 27–28.10 as an 'aquatic display' that offers Christ-believers a spectacle of navigating the stormy imperial world. It argues that Pliny's Panegyricus similarly employs aquatic displays to instruct in negotiating the emperor Trajan's power. It identifies four means in Acts 27 that assert Rome's power – judicial, military, economic, and the sea as a contested site where the sovereignties of God and Rome compete and cooperate – and which Christ-believers must negotiate by various means including submission, awareness of danger, courage, social interaction, agency, contribution to well-being, and discernment of and contestive allegiance to God's greater sovereignty.